Use of oocyte transfer in a commercial breeding program for mares with reproductive abnormalities - Carnevale, E. M.; Squires, E. L.; Maclellan, L. J.; Alvarenga, Marco Antonio [UNESP]; Scott, T. J. (Amer Veterinary Medical Assoc, 2001)
In some mares with lesions of the reproductive tract, embryo collection and survival rates are low or collection of embryos is not feasible. For these mares, oocyte transfer has been proposed as a method to induce pregnancies. In this report, a method for oocyte transfer in mares and results of oocyte transfer performed over 2 breeding seasons, using mares with long histories of subfertility and various reproductive lesions, are described.Human chorionic gonadotropin or an implant containing a gonadotropin-releasing hormone analog was used to initiate follicular and oocyte maturation. Oocytes were collected by means of transvaginal ultrasound-guided follicular aspiration. Following follicular aspiration, cumulus oocyte complexes were evaluated for cumulus expansion and signs of atresia; immature oocytes were cultured in vitro to allow maturation. The recipient's ovary and uterine tube (oviduct) were exposed through a flank laparotomy with the horse standing, and the oocyte was slowly deposited within the oviduct. Oocyte transfer was attempted in 38 mares between 9 and 30 years old during 2 successive breeding seasons. All mares had a history of reproductive failure while in breeding and embryo transfer programs. Twenty pregnancies were induced. Fourteen of the pregnant mares delivered live foals. Results suggest that oocyte transfer can be a successful method for inducing pregnancy in subfertile mares in a commercial setting..